Indole synthesis catalyst and preparation method thereof, and synthesis method of indole compound
By supporting the precious metal active components on the zinc oxide-modified silica support and introducing the second active component, the problem of insufficient activity and stability of the existing catalyst is solved, and an efficient, low-cost and environmentally friendly indole synthesis catalyst is achieved.
Patent Information
- Application Number
- CN202510353194.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-25
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2045-03-25
AI Technical Summary
The existing indole synthesis catalysts are insufficient in activity and stability, and the reaction temperature is high, which has problems of environmental pollution and high cost.
By supporting the first active component of the noble metal on the zinc oxide-modified silica support and introducing the second active component, the synergistic effect of the modified support, the first active component and the second active component is formed, and the activity and stability of the catalyst are improved.
The high activity and stability of the catalyst are achieved, the reaction temperature is reduced, the equipment investment and maintenance costs are reduced, and the environmental protection performance is good.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the field of catalysts, and in particular to an indole synthesis catalyst and a preparation method thereof, and a synthesis method of indole compounds. Background Art
[0002] Indole is a compound of pyrrole and benzene in parallel, also known as benzopyrrole. Indole and its derivatives are widely found in nature, mainly in natural flower oils, such as jasmine, bitter orange flower, daffodil, vanilla, etc. As an important chemical raw material, it has a wide range of applications in many fields such as agriculture, medicine, dyes, etc. It can not only be used as a raw material for spices (such as: for the blending of artificial flower essential oils) and synthetic dyes, but also as a high-efficiency plant growth regulator, bactericide, etc. It can also be used to synthesize vasodilators, antipyretic analgesics, stimulants, antihypertensives, antihistamines, etc.
[0003] Before the 1990s, industrial synthetic indole was mainly extracted from coal tar and wash oil fractions. The indole content in high-temperature coal tar is about 0.1-0.16%. Generally, the coal tar and wash oil fractions are washed with alkali and acid to obtain the methylnaphthalene fraction, which is then distilled and cut. The 225-256°C fraction is first collected, melted with potassium hydroxide, and then washed and extracted with benzene. Then, it is hydrolyzed at 50-70°C to obtain crude indole oil. The crude indole oil is further distilled, cooled, crystallized, and centrifuged to obtain refined indole. However, the indole obtained by this method has a strong odor, which greatly limits its application in industry, especially in the perfume industry. At the same time, the method has many separation steps and high costs, which also limits its industrial development.
[0004] The one-step catalytic synthesis of indole from aniline and ethylene glycol was proposed in the 1990s. The raw materials of this method are cheap and easy to obtain, the reaction steps are few, the production cost is low, and the reactants do not generate byproducts such as inorganic salts. It is the most economical one among many indole synthesis methods. In the prior art, the synthesis catalysts of indole and its derivatives are mainly divided into two categories: non-precious metal catalysts and precious metal catalysts. Non-precious metal catalysts mainly include cadmium compounds, lead compounds, silicon-copper oxides and solid catalysts containing other elements. Among them, non-precious metal cadmium and lead compounds are highly toxic and cause serious pollution to the environment during use. Therefore, they have been eliminated by industrialization. Although silicon-copper oxide catalysts are highly active, cheap, and do not pollute the environment, they have poor catalyst stability and serious deactivation. Other solid acid catalysts have low indole yields. Precious metal catalysts are mainly loaded with silver, palladium, ruthenium, rhodium, etc. Among them, the catalyst structures of ruthenium-based and rhodium-based catalysts are very complex, and sometimes ligands need to be added, and they are expensive. At the same time, there are problems such as high reaction temperature and easy deactivation of catalysts.
[0005] Therefore, how to prepare indole synthesis catalysts with high activity, high stability and low reaction temperature through simple and low-cost methods will be an important research direction in this field. Summary of the invention
[0006] The purpose of the present invention is to overcome the problem of insufficient activity and stability of indole synthesis catalysts in the prior art, and to provide an indole synthesis catalyst and a preparation method thereof, and a synthesis method of indole compounds. The indole synthesis catalyst prepared by the preparation method has high catalytic activity and good stability.
[0007] In order to achieve the above object, the present invention provides a method for preparing an indole synthesis catalyst, the preparation method comprising: (1) impregnating a silica support with a solution containing a zinc precursor, and then performing a first drying and a first calcination to obtain a modified support; (2) mixing a first slurry containing the modified support with a second solution containing a precursor of the first active component to obtain a mixed solution; Wherein, the first active component is selected from at least one of Ag, Pd and Ru; (3) contacting the mixed solution with a precipitant, controlling the pH to 8-10, performing a precipitation reaction, and then performing aging, a second drying, and a second roasting; (4) mixing the product obtained in step (3), the soluble compound of the second active component, and an optional binder and an optional peptizing agent, and performing molding, a third drying, and a third calcination; Wherein, the second active component is selected from at least one of Cu, Co, Ni and Fe.
[0008] The second aspect of the present invention provides an indole synthesis catalyst prepared by the above preparation method; The indole synthesis catalyst comprises a modified carrier, a first active component and a second active component; Wherein, the modified carrier comprises silicon dioxide and a modified component zinc; the first active component is selected from at least one of Ag, Pd and Ru; and the second active component is selected from at least one of Cu, Co, Ni and Fe.
[0009] The third aspect of the present invention provides a method for synthesizing an indole compound, the method comprising: contacting ethylene glycol, aniline and a catalyst in the presence of hydrogen and water; Wherein, the catalyst is the indole synthesis catalyst described in the second aspect.
[0010] Through the above technical scheme, the present invention proposes a new preparation method of indole synthesis catalyst, which loads the first active component of noble metal on the carrier modified by zinc oxide by precipitation impregnation method, so that the active component of the catalyst can be evenly distributed on the carrier, and then by introducing the second active component, the amount of the first active component can be reduced, the cost of the catalyst can be reduced, and the utilization efficiency of the active component of the catalyst can be significantly improved, and the sintering and agglomeration of the active component during the reaction can be effectively inhibited; the synergistic effect of the first active component, the second active component and the modified carrier can improve the anti-sintering performance of the active component, the stability is good during use, it is not easy to deactivate, the reaction temperature is low, the equipment investment cost and maintenance cost of the synthesis system of indole and its derivatives can be reduced, and it also has important application potential in the field of environmentally friendly chemical catalysis. The preparation method has a simple process flow, is conducive to large-scale production, and meets the demand for efficient and stable catalysts in the field of indole and its derivatives synthesis. DETAILED DESCRIPTION
[0011] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0012] The first aspect of the present invention provides a method for preparing an indole synthesis catalyst, the preparation method comprising: (1) impregnating a silica support with a solution containing a zinc precursor, and then performing a first drying and a first calcination to obtain a modified support; (2) mixing a first slurry containing the modified support with a second solution containing a precursor of the first active component to obtain a mixed solution; Wherein, the first active component is selected from at least one of Ag, Pd and Ru; (3) contacting the mixed solution with a precipitant, controlling the pH to 8-10, performing a precipitation reaction, and then performing aging, a second drying, and a second roasting; (4) mixing the product obtained in step (3), the soluble compound of the second active component, and an optional binder and an optional peptizing agent, and performing molding, a third drying, and a third calcination; Wherein, the second active component is selected from at least one of Cu, Co, Ni and Fe.
[0013] The silica carrier of the present invention has a wide selection range, and can be silica of any shape and size, for example, silica powder, which can be commercially available to those skilled in the art.
[0014] According to some preferred embodiments of the present invention, the specific surface area of the silica carrier is 400-700m 2 / g.
[0015] The inventors of the present invention have found in their research that first modifying the silica carrier with zinc oxide can help the subsequent active components to be more fully loaded on the carrier and avoid possible agglomeration or over-impregnation of the active components. The reason may be that the interaction between the active components and the silica carrier is weak, and they are easy to move, aggregate and sinter at a higher reaction temperature. Zinc oxide can be dispersed in a single layer on the silica. The introduction of zinc oxide can make the first active component particles added subsequently highly dispersed on the carrier, avoiding agglomeration and sintering, thereby improving the utilization rate of the active components in the catalyst and improving the overall performance of the catalyst.
[0016] According to some preferred embodiments of the present invention, the amount of zinc precursor calculated as zinc element is 1-10 parts by weight, preferably 3-7 parts by weight, relative to 100 parts by weight of the silica carrier, for example, it can be 3, 4, 5, 6, 7 parts by weight or any range between the two. The above preferred embodiments are conducive to the high dispersion of active components on the carrier surface, thereby improving the stability of the catalyst. Excessive zinc oxide may aggravate the side reaction and reduce the selectivity of indole.
[0017] The present invention has no particular limitation on the conditions for the impregnation in step (1), and any conventional conditions in the art may be used as long as the zinc component can be loaded onto the silica carrier.
[0018] According to some preferred embodiments of the present invention, the immersion temperature is 20-60° C., and the time is 1-6 h.
[0019] In the present invention, the solvent in the solution containing the zinc precursor is preferably water. The present invention has no particular limitation on the concentration of the solution, and those skilled in the art can select it according to the actual amount of metal required.
[0020] According to the present invention, preferably, the zinc precursor is selected from at least one of zinc nitrate, chloride nitrate, acetate, sulfate and chloride. The zinc precursor may also contain crystal water, and the present invention has no special requirements for this.
[0021] The present invention has no particular limitation on the method and conditions of the first drying. Preferably, the first drying is evaporative drying.
[0022] Preferably, the conditions for the first drying include: a temperature of 70-150° C., preferably 100-120° C., and a time of 1-24 h, preferably 2-6 h.
[0023] According to some preferred embodiments of the present invention, the conditions for the first calcination include: a temperature of 250-750° C., preferably 450-650° C., and a time of 0.5-10 h, preferably 3-6 h.
[0024] In the present invention, the first slurry containing the modified carrier and the second solution containing the precursor of the first active component are mixed to obtain a mixed solution in step (2), and then a precipitant is introduced to perform precipitation and impregnation, so that the active component can be substantially completely adsorbed on the surface of the carrier, thereby improving the utilization rate of the active component. The size of the catalyst particles obtained is relatively uniform step by step, and the catalytic activity of the obtained indole synthesis catalyst is further improved.
[0025] According to some preferred embodiments of the present invention, in step (2), based on the mass of the silica carrier in the modified carrier, the amount of the precursor of the first active component in terms of element is 0.1-30wt%, preferably 2-20wt%, and more preferably 4-15wt%.
[0026] According to some preferred embodiments of the present invention, the first active component is Ag.
[0027] According to the present invention, the first slurry further contains water to disperse the modified carrier. The present invention has no particular limitation on the amount of water in the first slurry, as long as it can play a dispersing role.
[0028] The present invention has no particular limitation on the solvent in the second solution, and water is preferred. The present invention has no particular limitation on the amount of the solvent in the second solution, and the amount is based on the ability to fully dissolve the precursor of the first active component and facilitate the impregnation loading of the first active component. Metallurgical personnel in the field can select the amount according to actual needs.
[0029] According to some preferred embodiments of the present invention, in step (2), the mixing conditions include: temperature of 40-90°C, preferably 65-85°C; time of 0.1-2h, preferably 0.5-1h. The above preferred embodiments are advantageous for the active components to be preferentially adsorbed on the surface of the carrier, thereby preventing precipitation nucleation from occurring in the solution rather than on the carrier.
[0030] According to the present invention, preferably, the mixing is performed under stirring conditions at a stirring rate of 100-500 rpm.
[0031] According to the present invention, in step (3), the pH is controlled to be 8-10, preferably 8.5-9.5, to carry out the precipitation reaction.
[0032] The present invention has a wide range of choices for the precipitant, and any conventional precipitant in the art can be applied to the present invention. Preferably, the precipitant is selected from at least one of ammonium bicarbonate, sodium carbonate, sodium hydroxide, ammonia water, and urea, preferably ammonium bicarbonate.
[0033] In the present invention, preferably, the precipitant is provided by an aqueous solution of the precipitant, and the concentration of the aqueous solution of the precipitant is 0.1-2 mol / L.
[0034] The precipitant can be contacted with the mixed solution by a conventional feeding device in the art such as a peristaltic pump, and the amount of the precipitant added is based on meeting the above pH requirement.
[0035] According to some preferred embodiments of the present invention, the aging temperature is 40-90°C, preferably 65-85°C, and the time is 4-24h, preferably 6-16h.
[0036] In the present invention, the preparation method may further include: washing the aged product until the filtrate is neutral, for example, the pH of the filtrate is 7, and the conductivity of the filtrate is less than 50 s / m. The washing may be performed in any conventional manner in the art, and the present invention has no particular requirements for this.
[0037] According to the present invention, preferably, in step (3), the second drying is evaporative drying, and the conditions for the second drying include: a temperature of 70-150° C., preferably 100-120° C., and a time of 1-24 h, preferably 2-6 h.
[0038] According to the present invention, preferably, the conditions for the second calcination include: a temperature of 300-1000° C., preferably 350-650° C., and a time of 0.5-10 h, preferably 3-6 h.
[0039] The present invention has no particular limitation on the type of the soluble compound of the second active component, as long as it can provide the second active component, for example, it can be nitrate, acetate, sulfate, chloride, etc. containing the second active component.
[0040] According to some preferred embodiments of the present invention, in step (4), based on the mass of the silica carrier in the product obtained in step (3), the amount of the soluble compound of the second active component calculated as an element is 0.01-20wt%, preferably 3-15wt%, and preferably 5-10wt%.
[0041] According to some preferred embodiments of the present invention, the second active component is Cu.
[0042] According to some particularly preferred embodiments of the present invention, the first active component is Ag, and the second active component is Cu. The combination of the first active component and the second active component can further improve the catalyst reaction activity and the indole yield.
[0043] In the present invention, those skilled in the art can optionally add a binder and a peptizing agent according to the needs of molding. The present invention has no particular limitation on the types of the binder and the peptizing agent, which can be conventionally selected in the art.
[0044] According to the present invention, preferably, the binder is selected from at least one of sesbania powder, starch, methyl cellulose and cellulose powder, preferably sesbania powder.
[0045] Preferably, the mass ratio of the binder to the product obtained in step (3) is (1-5):100.
[0046] Preferably, the peptizing agent is selected from at least one of nitric acid, hydrochloric acid and ammonia water, preferably nitric acid.
[0047] Preferably, the mass ratio of the peptizing agent to the product obtained in step (3) is (1-5):100.
[0048] In the present invention, there is no particular limitation on the molding method in step (4), and those skilled in the art can select it according to actual needs. For example, it can be extrusion molding.
[0049] According to the present invention, preferably, in step (4), the temperature of the third calcination is 300-1000°C, preferably 350-650°C, and the time is 0.5-10h, preferably 3-6h.
[0050] According to some preferred embodiments of the present invention, the preparation method further comprises: subjecting the product of the third calcination to a reduction treatment in the presence of hydrogen. The present invention has a wide range of selection conditions for the reduction treatment, and is based on the ability to reduce at least part of the active components to simple substances. Those skilled in the art can select according to actual needs.
[0051] According to the present invention, preferably, the reduction treatment conditions include: a temperature of 250-450° C., preferably 280-320° C., and a time of 1-6 h, preferably 2-4 h.
[0052] The second aspect of the present invention provides an indole synthesis catalyst prepared by the above preparation method.
[0053] According to the present invention, the indole synthesis catalyst comprises a modified carrier, a first active component and a second active component; Wherein, the modified carrier comprises silicon dioxide and a modified component zinc; the first active component is selected from at least one of Ag, Pd and Ru; and the second active component is selected from at least one of Cu, Co, Ni and Fe.
[0054] According to the present invention, preferably, based on the mass of the modified carrier, the content of the first active component in terms of element is 0.1-30wt%, preferably 2-20wt%, and more preferably 4-15wt%; the content of the second active component in terms of element is 0.01-20wt%, preferably 3-15wt%, and more preferably 5-10wt%; the content of the modified component zinc is 1-10wt%, preferably 3-7wt%.
[0055] Preferably, the mass ratio of the first active component calculated as an element to the second active component calculated as an element is 1:(1-3), preferably 1:(1.2-2). In the above preferred case, it is beneficial to further improve the conversion rate and selectivity of the catalyst.
[0056] The third aspect of the present invention provides a method for synthesizing an indole compound, the method comprising: contacting ethylene glycol, aniline and a catalyst in the presence of hydrogen and water; Wherein, the catalyst is the indole synthesis catalyst described in the second aspect.
[0057] According to some preferred embodiments of the present invention, the contact conditions include: reaction temperature of 200-320°C, preferably 270-290°C; reaction pressure of 0.01-1MPa, preferably 0.05-0.2MPa; molar ratio of aniline to ethylene glycol of (1-15):1, preferably (5-10):1; volumetric space velocity of the total material of aniline and ethylene glycol of 0.01-1h -1 , preferably 0.1-0.6h -1 ; The volume space velocity of water feed is 0.01-1h -1 , preferably 0.1-1 h -1 ; The volume space velocity of hydrogen is 0.1-20h -1 , preferably 0.2-10 h -1 .
[0058] The above preferred reaction conditions are used to inhibit the rate of carbon deposition, slow down the rate of catalyst deactivation, and improve the indole yield.
[0059] The present invention will be described in detail below through examples.
[0060] Unless otherwise specified, the raw materials used in the following examples and comparative examples are commercially available.
[0061] The specific surface area of the silicon oxide powder used in the following examples is 660 m 2 / g.
[0062] Example 1 1. Place 100 g of commercial silicon oxide powder in a beaker, dissolve 22.75 g of zinc nitrate hexahydrate in deionized water to obtain a first mixed solution, pour the first mixed solution into the silicon oxide powder, soak for 2 hours, dry at 120° C. for 2 hours, and calcine at 500° C. for 4 hours to obtain a modified carrier.
[0063] 2. Disperse the modified carrier in deionized water to form a first slurry under mechanical stirring. Add 9.449 g of silver nitrate solution (concentration 50 wt%) into deionized water to obtain a second mixed solution, pour the second mixed solution into the first slurry, stir and immerse for 0.5 h at 80°C and 300 rpm to obtain a second mixed slurry.
[0064] 3. Use a peristaltic pump to drop 1 mol / L ammonium bicarbonate solution into the second mixed slurry to control the end point pH=9. Then age at 80°C for 8h. After aging, filter the precipitate and wash the filter cake with deionized water until the filtrate pH=7 and the conductivity is less than 50. Then place the filter cake in an oven at 120°C and dry to constant weight, then calcine at 500°C for 4h to obtain a composite oxide.
[0065] 4. The composite oxide, 3.5 g of sesbania powder, 2.5 g of nitric acid, and 30.419 g of copper nitrate trihydrate are mixed, and the resulting mixture is kneaded and extruded into strips. The extruded strips are allowed to stand at room temperature for 2 h, then dried at 120° C. to constant weight, and calcined at 500° C. for 4 h to obtain the catalyst precursor.
[0066] 5. The catalyst precursor was placed in a 450°C tubular furnace for reduction in a hydrogen atmosphere for 4 hours to obtain a catalyst. Based on the mass of silicon dioxide, the composition of the catalyst according to ICP analysis was: Ag content was 3.01wt%, Cu content was 7.98wt%, and Zn content was 5.01wt%.
[0067] Example 2 1. Place 100 g of commercial silicon oxide powder in a beaker, dissolve 22.75 g of zinc nitrate hexahydrate in deionized water to obtain a first mixed solution, pour the first mixed solution into the silicon oxide powder, soak for 2 hours, dry at 120° C. for 2 hours, and calcine at 500° C. for 4 hours to obtain a modified carrier.
[0068] 2. Disperse the modified carrier in deionized water to form a first slurry under mechanical stirring. Add 12.599 g of silver nitrate solution (concentration 50 wt%) into deionized water to obtain a second mixed solution, pour the second mixed solution into the first slurry, stir and immerse at 80°C and 300 rpm for 1 hour to obtain a second mixed slurry.
[0069] 3. Use a peristaltic pump to drop 1 mol / L ammonium bicarbonate solution into the second mixed slurry to control the end point pH=9. Then age at 80°C for 8h. After aging, filter the precipitate and wash the filter cake with deionized water until the filtrate pH=7 and the conductivity is less than 50. Then place the filter cake in an oven at 120°C and dry to constant weight, then calcine at 500°C for 4h to obtain a composite oxide.
[0070] 4. Mix the composite oxide, 3.5 g of sesbania powder, 2.5 g of nitric acid, and 30.419 g of copper nitrate trihydrate, and knead the resulting mixture into strips. Let the extruded strips stand at room temperature for 2 hours, then dry at 120°C to constant weight, and calcine at 500°C for 4 hours to obtain the catalyst precursor.
[0071] 5. The catalyst precursor was placed in a 450°C tubular furnace for reduction in a hydrogen atmosphere for 4 hours to obtain a catalyst. Based on the mass of the carrier, the composition of the catalyst according to ICP analysis was: Ag content was 3.99wt%, Cu content was 8.02wt%, and Zn content was 4.99wt%.
[0072] Example 3 1. Place 100 g of commercial silicon oxide powder in a beaker, dissolve 22.75 g of zinc nitrate hexahydrate in deionized water to obtain a first mixed solution, pour the first mixed solution into the silicon oxide powder, soak for 2 hours, dry at 120° C. for 2 hours, and calcine at 500° C. for 4 hours to obtain a modified carrier.
[0073] 2. Dissolve the modified carrier in deionized water to form a first slurry under mechanical stirring. Add 15.749 g of silver nitrate solution (concentration 50 wt%) into deionized water to obtain a second mixed solution, pour the second mixed solution into the first slurry, stir and immerse for 2 h at 80°C and 300 rpm to obtain a second mixed slurry.
[0074] 3. Use a peristaltic pump to drop 1 mol / L ammonium bicarbonate solution into the second mixed slurry to control the end point pH=9. Then age at 80°C for 8h. After aging, filter the precipitate and wash the filter cake with deionized water until the filtrate pH=7 and the conductivity is less than 50. Then place the filter cake in an oven at 120°C and dry to constant weight, and then calcine at 500°C for 4h to obtain a composite oxide.
[0075] 4. Mix the composite oxide, 3.5 g of sesbania powder, 2.5 g of nitric acid, and 30.419 g of copper nitrate trihydrate, and knead the resulting mixture into strips. Let the extruded strips stand at room temperature for 2 hours, then dry at 120°C to constant weight, and calcine at 500°C for 4 hours to obtain the catalyst precursor.
[0076] 5. The catalyst precursor was placed in a 450°C tubular furnace for reduction under a hydrogen atmosphere for 4 hours to obtain a catalyst. Based on the mass of the carrier, the composition of the catalyst according to ICP analysis was: Ag content was 5.02wt%, Cu content was 8.01wt%, and Zn content was 4.97wt%.
[0077] Example 4 1. Place 100 g of commercial silicon oxide powder in a beaker, dissolve 18.20 g of zinc nitrate hexahydrate in deionized water to obtain a first mixed solution, pour the first mixed solution into the silicon oxide powder, soak for 2 hours, dry at 150° C. for 1 hour, and calcine at 550° C. for 4 hours to obtain a modified carrier.
[0078] 2. Dissolve the modified carrier in deionized water to form a first slurry under mechanical stirring. Add 18.899 g of silver nitrate solution (concentration 50 wt%) into deionized water to obtain a second mixed solution, pour the second mixed solution into the first slurry, stir and immerse for 1 hour at 60°C and 300 rpm to obtain a second mixed slurry.
[0079] 3. Use a peristaltic pump to drop 1 mol / L ammonium bicarbonate solution into the second mixed slurry, and control the end point pH=8.5. Then age at 85°C for 8h. After aging, filter the precipitate and wash the filter cake with deionized water until the filtrate pH=7 and the conductivity is less than 50. Then place the filter cake in an oven at 110°C and dry it to constant weight, and then calcine at 600°C for 4h to obtain a composite oxide.
[0080] 4. Mix the composite oxide, 4 g of sesbania powder, 2 g of nitric acid, and 30.419 g of copper nitrate trihydrate, and knead the resulting mixture into strips. Let the extruded strips stand at room temperature for 2 hours, then dry at 120°C to constant weight, and calcine at 600°C for 3 hours to obtain the catalyst precursor.
[0081] 5. The catalyst precursor was placed in a 450°C tubular furnace for reduction in a hydrogen atmosphere for 4 hours to obtain a catalyst. Based on the mass of the carrier, the composition of the catalyst according to ICP analysis was: Ag content was 6.01wt%, Cu content was 7.97wt%, and Zn content was 4wt%.
[0082] Example 5 1. Place 100 g of commercial silicon oxide powder in a beaker, dissolve 31.85 g of zinc nitrate hexahydrate in deionized water to obtain a first mixed solution, pour the first mixed solution into the silicon oxide powder, soak for 2 hours, dry at 120° C. for 2 hours, and calcine at 450° C. for 6 hours to obtain a modified carrier.
[0083] 2. Dissolve the modified carrier in deionized water to form a first slurry under mechanical stirring. Add 15.749 g of silver nitrate solution (concentration 50 wt%) into deionized water to obtain a second mixed solution, pour the second mixed solution into the first slurry, stir and immerse for 1 hour at 70°C and 300 rpm to obtain a second mixed slurry.
[0084] 3. Use a peristaltic pump to drop 1 mol / L ammonium bicarbonate solution into the second mixed slurry, and control the end point pH=9. Then age at 80°C for 8h. After aging, filter the precipitate and wash the filter cake with deionized water until the filtrate pH=7 and the conductivity is less than 50. Then place the filter cake in an oven at 120°C and dry it to constant weight, and then calcine at 400°C for 5h to obtain a composite oxide.
[0085] 4. Mix the composite oxide, 3.5 g of sesbania powder, 2.5 g of nitric acid, and 22.814 g of copper nitrate trihydrate, and knead the resulting mixture into strips. Let the extruded strips stand at room temperature for 2 hours, then dry at 120°C to constant weight, and calcine at 650°C for 4 hours to obtain the catalyst precursor.
[0086] 5. The catalyst precursor was placed in a 450°C tubular furnace for reduction in a hydrogen atmosphere for 4 hours to obtain a catalyst. Based on the mass of the carrier, the composition of the catalyst according to ICP analysis was: Ag content was 4.99wt%, Cu content was 6.02wt%, and Zn content was 7wt%.
[0087] Example 6 1. Place 100 g of commercial silicon oxide powder in a beaker, dissolve 22.75 g of zinc nitrate hexahydrate in deionized water to obtain a first mixed solution, pour the first mixed solution into the silicon oxide powder, soak for 2 hours, dry at 120° C. for 2 hours, and calcine at 500° C. for 4 hours to obtain a modified carrier.
[0088] 2. Dissolve the modified carrier in deionized water to form a first slurry under mechanical stirring. Add 15.749 g of silver nitrate solution (concentration 50%) into deionized water to obtain a second mixed solution, pour the second mixed solution into the first slurry, stir and immerse for 0.5 h at 80°C and 300 rpm to obtain a second mixed slurry.
[0089] 3. Use a peristaltic pump to drop 1 mol / L ammonium bicarbonate solution into the second mixed slurry to control the end point pH=9. Then age at 80°C for 8h. After aging, filter the precipitate and wash the filter cake with deionized water until the filtrate pH=7 and the conductivity is less than 50. Then place the filter cake in an oven at 120°C and dry to constant weight, and then calcine at 500°C for 4h to obtain a composite oxide.
[0090] 4. Mix the composite oxide, 3.5 g of sesbania powder, 2.5 g of nitric acid, and 26.616 g of copper nitrate trihydrate, and knead the resulting mixture into strips. Let the extruded strips stand at room temperature for 2 hours, then dry at 120°C to constant weight, and calcine at 500°C for 4 hours to obtain the catalyst precursor.
[0091] 5. The catalyst precursor was placed in a 450°C tubular furnace under a hydrogen atmosphere for 4 hours to obtain a catalyst. Based on the mass of the carrier, the composition of the catalyst according to ICP analysis was: Ag content was 5.01wt%, Cu content was 6.99wt%, and Zn content was 5.00wt%.
[0092] Example 7 1. Place 100 g of commercial silicon oxide powder in a beaker, dissolve 22.75 g of zinc nitrate hexahydrate in deionized water to obtain a first mixed solution, pour the first mixed solution into the silicon oxide powder, soak for 2 hours, dry at 120° C. for 2 hours, and calcine at 500° C. for 4 hours to obtain a modified carrier.
[0093] 2. Dissolve the modified carrier in (1) in deionized water to form a first slurry under mechanical stirring. Add 15.749 g of silver nitrate solution (concentration 50%) into deionized water to obtain a second mixed solution, pour the second mixed solution into the first slurry, stir and immerse for 0.58 h at 80°C and 300 rpm to obtain a second mixed slurry.
[0094] 3. Use a peristaltic pump to drop 1 mpl / L ammonium bicarbonate solution into the second mixed slurry to control the end point pH = 9. Then age at 80°C for 8 hours. After aging, filter the precipitate and wash the filter cake with deionized water until the filtrate pH = 7 and the conductivity is <50. Then place the filter cake in an oven at 120°C and dry to constant weight, and calcine at 500°C for 4 hours to obtain a composite oxide.
[0095] 4. Mix the composite oxide, 3.5 g of sesbania powder, 2.5 g of nitric acid, and 34.221 g of copper nitrate trihydrate, and knead the resulting mixture into strips. Let the extruded strips stand at room temperature for 2 hours, then dry at 120°C to constant weight, and calcine at 500°C for 4 hours to obtain the catalyst precursor.
[0096] 5. The catalyst precursor was placed in a 450°C tubular furnace for reduction under a hydrogen atmosphere for 4 hours to obtain a catalyst. Based on the mass of the carrier, the composition of the catalyst according to ICP analysis was: Ag content was 5.02wt%, Cu content was 8.97wt%, and Zn content was 5.01wt%.
[0097] Comparative Example 1 1. Place 100 g of commercial silicon oxide powder in a beaker, dissolve 22.75 g of zinc nitrate hexahydrate in deionized water to obtain a first mixed solution, pour the first mixed solution into the silicon oxide powder, soak for 2 hours, dry at 120° C. for 2 hours, and calcine at 500° C. for 4 hours to obtain a modified carrier.
[0098] 2. The modified carrier, 3.5 g of sesbania powder, 2.5 g of nitric acid, and 30.419 g of copper nitrate trihydrate were mixed, and the resulting mixture was kneaded and extruded into strips. The extruded strips were allowed to stand at room temperature for 2 h, then dried at 120° C. to constant weight, and calcined at 500° C. for 4 h to obtain the catalyst precursor.
[0099] 3. The catalyst precursor was placed in a 450°C tubular furnace for reduction in a hydrogen atmosphere for 4 hours to obtain a catalyst. Based on the mass of the carrier, the composition of the catalyst according to ICP analysis was: the content of Cu was 8.01wt%, and the content of Zn was 4.99wt%.
[0100] Comparative Example 2 1. Place 100 g of commercial silicon oxide powder in a beaker, dissolve 22.75 g of zinc nitrate hexahydrate in deionized water to obtain a first mixed solution, pour the first mixed solution into the silicon oxide powder, soak for 2 hours, dry at 120° C. for 2 hours, and calcine at 500° C. for 4 hours to obtain a modified carrier.
[0101] 2. Dissolve the modified carrier in (1) in deionized water to form a first slurry under mechanical stirring. Add 15.749 g of silver nitrate solution (concentration 50%) into deionized water to obtain a second mixed solution, pour the second mixed solution into the first slurry, stir and immerse at 80°C and 300 rpm for 0.5 h to obtain a second mixed slurry.
[0102] 3. Use a peristaltic pump to drop 1 mol / L ammonium bicarbonate solution into the second mixed slurry to control the end point pH=9. Then age at 80°C for 8h. After aging, filter the precipitate and wash the filter cake with deionized water until the filtrate pH=7 and the conductivity is less than 50. Then place the filter cake in an oven at 120°C and dry to constant weight, and calcine at 500°C for 4h to obtain a composite oxide.
[0103] 4. Mix the composite oxide, 3.5 g of sesbania powder and 2.5 g of nitric acid, knead the mixture and extrude it into strips. Let the extruded strips stand at room temperature for 2 hours, then dry them at 120°C to constant weight, and calcine them at 500°C for 4 hours to obtain the catalyst precursor.
[0104] 5. The catalyst precursor was placed in a 450°C tubular furnace under a hydrogen atmosphere for 4 hours to obtain a catalyst. Based on the mass of the carrier, the composition of the catalyst according to ICP analysis was: Ag content was 5.01wt%, and Zn content was 4.99wt%.
[0105] Comparative Example 3 1. Dissolve 100g of commercial silicon oxide powder in deionized water to form a first slurry under mechanical stirring. Add 15.749g of silver nitrate solution (concentration 50%) into deionized water to obtain a first mixed solution, pour the first mixed solution into the first slurry, stir and immerse for 0.5h at 80°C and 300rpm to obtain a second mixed slurry.
[0106] 2. Use a peristaltic pump to drop 1 mol / L ammonium bicarbonate solution into the second mixed slurry to control the end point pH=9. Then age at 80°C for 8h. After aging, filter the precipitate and wash the filter cake with deionized water until the filtrate pH=7 and the conductivity is less than 50. Then place the filter cake in an oven at 120°C and dry to constant weight, and calcine at 500°C for 4h to obtain a composite oxide.
[0107] 3. Mix the composite oxide, 3.5 g of sesbania powder, 2.5 g of nitric acid, and 34.221 g of copper nitrate trihydrate, and knead the resulting mixture into strips. Let the extruded strips stand at room temperature for 2 hours, then dry at 120°C to constant weight, and calcine at 500°C for 4 hours to obtain the catalyst precursor.
[0108] 4. The catalyst precursor was placed in a 450°C tubular furnace for reduction under a hydrogen atmosphere for 4 hours to obtain a catalyst. Based on the mass of the carrier, the composition of the catalyst according to ICP analysis was: Ag content was 5.02wt%, and Cu content was 8.97wt%.
[0109] Comparative Example 4 1. Place 100 g of commercial silicon oxide powder in a beaker, dissolve 22.75 g of zinc nitrate hexahydrate in deionized water to obtain a first mixed solution, pour the first mixed solution into the silicon oxide powder, soak for 2 hours, dry at 120° C. for 2 hours, and calcine at 500° C. for 4 hours to obtain a modified carrier.
[0110] 2. Dissolve the modified support in deionized water to form a first slurry under mechanical stirring. Add 15.749 g of silver nitrate solution (concentration 50 wt%) to deionized water to obtain a second mixed solution, add 30.419 g of copper nitrate trihydrate to deionized water to obtain a third mixed solution, pour the second and third mixed solutions into the first slurry, stir and immerse at 80°C and 300 rpm for 2 hours to obtain a second mixed slurry.
[0111] 3. Use a peristaltic pump to drop 1 mol / L ammonium bicarbonate solution into the second mixed slurry to control the end point pH=9. Then age at 80°C for 8h. After aging, filter the precipitate and wash the filter cake with deionized water until the filtrate pH=7 and the conductivity is less than 50. Then place the filter cake in an oven at 120°C and dry to constant weight, and then calcine at 500°C for 4h to obtain a composite oxide.
[0112] 4. Mix the composite oxide, 3.5 g of sesbania powder and 2.5 g of nitric acid, knead the mixture and extrude it into strips. Let the extruded strips stand at room temperature for 2 hours, then dry them at 120°C to constant weight, and calcine them at 500°C for 4 hours to obtain the catalyst precursor.
[0113] 5. The catalyst precursor was placed in a 450°C tubular furnace for reduction under a hydrogen atmosphere for 4 hours to obtain a catalyst. Based on the mass of the carrier, the composition of the catalyst according to ICP analysis was: Ag content was 4.89wt%, Cu content was 8.01wt%, and Zn content was 4.99wt%.
[0114] Test Case Test Example 1 Activity Test: The catalyst prepared in the above examples and comparative examples was crushed and sieved to obtain 20-40 mesh catalyst, 100 mL of which was loaded into a fixed bed reactor. After the catalyst was kept at a constant temperature of 290 ° C in a pure hydrogen atmosphere at normal pressure in the reactor for 4 hours, the raw materials and water were transported to the preheater by a feed pump. The raw materials, water and hydrogen were mixed and preheated in the preheater and then entered the reactor for reaction. After the reaction product was separated by gas and liquid, the liquid product entered the product tank for enrichment. Under the reaction conditions of 290 ° C, 0.2 MPa, and a molar ratio of aniline to ethylene glycol of 7:1, the hourly space velocity of the reaction liquid of the mixed solution of aniline and ethylene glycol was 0.2h -1 , the hydrogen volume space velocity is 0.2h -1 , the hourly space velocity of water reaction liquid is 0.2h -1 The results of the 4 h reaction are shown in Table 1.
[0115] Table 1
[0116] Test Example 2 Catalyst life test: The catalyst prepared in Example 3 and Comparative Example 3 was crushed and screened to obtain 100 mL of 20-40 mesh catalyst and loaded into a fixed bed reactor. After the catalyst was kept at a constant temperature of 290 ° C in a pure hydrogen atmosphere at normal pressure in the reactor for 4 hours, the raw materials and water were transported to the preheater by a feed pump. The raw materials, water and hydrogen were mixed and preheated in the preheater and then entered the reactor for reaction. After the reaction product was separated by gas and liquid, the liquid phase product entered the product tank for enrichment. Under the reaction conditions of 290 ° C, 0.2 MPa, and a molar ratio of aniline to ethylene glycol of 7:1, the hourly space velocity of the reaction liquid of the mixed solution of aniline and ethylene glycol was 0.2h -1 , the hydrogen volume space velocity is 0.2h -1 , the hourly space velocity of water reaction liquid is 0.2h -1 The analysis results are shown in Table 2.
[0117] Table 2
[0118] As can be seen from the above table, the conversion rate and selectivity of the embodiment are both above 80%, indicating that the preparation method provided by the present invention effectively reduces the loading amount of the precious metal by introducing a certain amount of non-precious metal to replace the precious metal, and significantly improves the reaction activity and stability of the catalyst. Compared with Comparative Example 3, the conversion rate of the catalyst in Example 3 remained at 100% after running for 72 hours, and the selectivity was stable at about 83-85%, indicating that the carrier was modified by introducing a zinc oxide additive, which effectively suppressed the deactivation of the catalyst during the reaction and improved the stability of the catalyst.
[0119] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for preparing an indole synthesis catalyst, characterized in that: The preparation method comprises: (1) impregnating a silica support with a solution containing a zinc precursor, and then performing a first drying and a first calcination to obtain a modified support; (2) mixing a first slurry containing the modified support with a second solution containing a precursor of the first active component to obtain a mixed solution; Wherein, the first active component is selected from at least one of Ag, Pd and Ru; (3) contacting the mixed solution with a precipitant, controlling the pH to 8-10, performing a precipitation reaction, and then performing aging, a second drying, and a second roasting; (4) mixing the product obtained in step (3), the soluble compound of the second active component, and an optional binder and an optional peptizing agent, and performing molding, a third drying, and a third calcination; Wherein, the second active component is selected from at least one of Cu, Co, Ni and Fe.
2. The preparation method according to claim 1, wherein The specific surface area of the silica carrier is 400-700m 2 / g; The amount of the zinc precursor calculated as zinc element is 1-10 parts by weight relative to 100 parts by weight of the silica carrier.
3. The preparation method according to claim 1 or 2, wherein The first drying is evaporative drying, and the conditions of the first drying include: a temperature of 70-150° C. and a time of 1-24 hours; The first calcination conditions include: temperature of 250-750° C. and time of 0.5-10 h.
4. The preparation method according to claim 1 or 2, wherein: In step (2), the amount of the precursor of the first active component calculated as an element is 0.1-30wt% based on the mass of the silica carrier in the modified carrier; The first active component is Ag.
5. The preparation method according to claim 1 or 2, wherein: In step (2), the mixing conditions include: temperature of 40-90°C and time of 0.1-2h; The mixing is carried out under stirring conditions, and the stirring rate is 100-500 rpm.
6. The preparation method according to claim 1 or 2, wherein: In step (3), the precipitant is selected from at least one of ammonium bicarbonate, ammonium carbonate, sodium hydroxide, ammonia water, and urea; The precipitant is provided by an aqueous solution of the precipitant, and the concentration of the aqueous solution of the precipitant is 0.1-2 mol / L.
7. The preparation method according to claim 1 or 2, wherein: The aging temperature is 40-90°C and the time is 4-24h; The preparation method may further optionally include: washing the aged product until the filtrate is neutral and the conductivity of the filtrate is less than 50 s / m; In step (3), the second drying is evaporative drying, and the conditions of the second drying include: temperature of 70-150° C. and time of 1-24 h; The conditions of the second calcination include: a temperature of 300-1000° C. and a time of 0.5-10 h.
8. The preparation method according to claim 1 or 2, wherein: In step (4), based on the mass of the silica carrier in the product obtained in step (3), the amount of the soluble compound of the second active component calculated as an element is 0.01-20wt%; The second active component is Cu.
9. The preparation method according to claim 1 or 2, wherein: The binder is selected from at least one of sesbania powder, starch, methyl cellulose and cellulose powder; The mass ratio of the binder to the product obtained in step (3) calculated as the silica carrier is (1-5): 100; The peptizing agent is selected from at least one of nitric acid, hydrochloric acid and ammonia water; The mass ratio of the peptizing agent to the product obtained in step (3) calculated as the silica carrier is (1-5): 100; In step (4), the temperature of the third calcination is 300-1000°C and the time is 0.5-10h.
10. The preparation method according to claim 1 or 2, wherein: The preparation method further comprises: subjecting the third calcined product to a reduction treatment in the presence of hydrogen; The reduction treatment conditions include: temperature of 250-450° C. and time of 1-6 h.
11. An indole synthesis catalyst obtained by the preparation method according to any one of claims 1 to 10; The indole synthesis catalyst comprises a modified carrier, a first active component and a second active component; in, The modified carrier comprises silicon dioxide and a modified component zinc; the first active component is selected from at least one of Ag, Pd and Ru; and the second active component is selected from at least one of Cu, Co, Ni and Fe.
12. The indole synthesis catalyst according to claim 11, wherein Based on the mass of silicon dioxide, the content of the first active component calculated as an element is 0.1-30wt%, the content of the second active component calculated as an element is 0.01-20wt%, and the content of the modifying component zinc is 1-10wt%.
13. A method for synthesizing an indole compound, characterized in that: The synthesis method comprises: contacting ethylene glycol, aniline and a catalyst in the presence of hydrogen and water; Wherein, the catalyst is the indole synthesis catalyst according to claim 11 or 12.
14. The synthesis method according to claim 13, wherein The contact conditions include: reaction temperature of 200-320°C, reaction pressure of 0.01-1MPa, molar ratio of aniline to ethylene glycol of (1-15):1, volumetric space velocity of the total material of aniline and ethylene glycol of 0.01-1h -1 , the volume space velocity of water feed is 0.01-1h -1 , the volume space velocity of hydrogen is 0.1-20h -1 .
Citation Information
Patent Citations
Catalyst for synthesis of indole and its preparation method
CN101007277A
Catalyst for preparing ethanol through hydrogenation of acetic ester and preparation method and application of catalyst
CN102327774A
Regeneration and activation method for producing benzpyrole catalyst
CN103537300A
Method for preparing 5, 6-dihydroxyindole by using modified ordered mesoporous carbon supported metal catalyst
CN112724064A
Method for producing indole compound
JP2002155051A
Cited By
Preparation method of indole
CN122344151A